A new method for determining the total electron content in Mars' ionosphere based on Mars Express MARSIS data. (March 2020) - Conroy, Philip; Quinsac, Gary; Floury, Nicolas; Witasse, Olivier; Cartacci, Marco; Orosei, Roberto; Kofman, Wlodek; Sánchez-Cano, Beatriz
Abstract: We present a new method for determining the total electron content (TEC) in the Martian ionosphere based on the time delay of received radar pulses of the Mars Advanced Radar for Subsurface and Ionospheric Sounding (MARSIS) on board the Mars Express spacecraft. Previous studies of the same dataset have produced differing results for the day-side ionosphere, so it is useful to have an alternative way to compute the TEC in this region. This method iterates a model ionosphere in order to simultaneously match the ionospheric delays of the signals received by the radar's two channels by finding the model which minimizes the root mean square error (RMSE) between the measured and simulated delays. Topographical information is obtained from data from the Mars Orbiter Laser Altimeter (MOLA) instrument. The model parameters are held constant for a given orbit, and a very good agreement between the simulated and measured delays is obtained. The TEC can then be inverted from the ionospheric model. Matching the delays of both channels simultaneously applies an additional constraint to the model which has not been made in previous studies. The model is additionally validated by matching the simulated pulses with the raw range-compressed measurements for one orbit. Finally, typical model parameters are compared to those obtained by previous studies, which are also simulated. The method is applied to orbits during moderate solar activity, and results show very good agreement with previous studies.